Dynamic lateral mass impact on steel stringer-stiffened cylinders. (June 2018) - Do, Quang Thang; Muttaqie, Teguh; Shin, Hyun Kyoung; Cho, Sang-Rai
Highlights: Dynamic mass impact tests have been performed to investigate the response of stringer-stiffened cylinders. Numerical simulations of the impact response of the stringer-stiffened cylinders are conducted. The effects of the strain-rate hardening definition on the numerical results are highlighted. Parametric studies were conducted on stringer-stiffened cylinder models to clarify the effect of boundary conditions, impact velocities, impact locations, stringer-stiffeners as well as striker header shapes. Abstract: This paper focuses on the impact responses of large-diameter, thin-walled steel stringer-stiffened cylinders subjected to low-velocity mass impact. The impact scenarios employed in this study represent load actions as a result of supply vessel collisions with the main legs of floating offshore platforms and wind turbine structures. Two steel stringer-stiffened cylinders were fabricated and drop tests were performed at mid-span, using a rigid knife-edged indenter. The details of the experimental setup, test procedure and test results are reported in this paper. The experimental data appear to be useful for future benchmark studies. Numerical predictions of the impact response of the test models were simulated by means of the explicit solver of the finite element software package ABAQUS. The numerical predictions show a good agreement with the test results. The effect of the strain-rate hardening definition on the results is highlighted. Furthermore, parametric studies were conducted on stringer-stiffened cylinder models in order to clarify the progressive impact responses.